Hubungan Dukungan Suami Dalam Pemilihan Alat Kontrasepsi IUD Di Wilayah Kerja Pauskesmas Ratahan - Sanjang, Meilany Leidy; Ilmiah, Widia Shofa; Maulina, Rifzul (NHM PRESS, 2024)
The population growth rate in Indonesia is estimated to reach 2.32 billion by 2020. There needs to be an effort to prevent population explosion by means of Family Planning (KB). The use of Long-Term Contraceptive Method (MKJP) is considered more effective in preventing pregnancy. Intra Uterine Device (IUD) belongs to the MKJP group. The study aims to determine the relationship between husband support and the use of IUD contraceptives in the Ratahan Health Center work area in 2024. This type of research is quantitative research, the design used is correlational, and uses a crosssecsional approach. Sampling with a total sampling of 33 people. Univariate analysis uses frequency stimulation, and bivariate uses Chi-Square analysis. Based on the results of the chi-square statistical test shows a relationship between the husband's knowledge of the use of IUD contraceptives with the value of Pearson Chisquare: .000 that there is a relationship between husband support and the selection of IUD contraceptives in the work area of the Ratahan Health Center. Advice given to mothers and husbands to always communicate about the desired contraceptives, besides that health workers provide information related to the use of IUDs to wives and husbands